A Study of major secure SDLC processes in web based applications - Mohanty, Subhranshu; Kumar Mohapatra, Amar; Patnaik, Srikanta (International Journal of Engineering and Technology, 2018)
Web applications have become important but there are different types of security problems which could lead to tampering with details. The most common are cookies poisoning, structured query language, cross-site scripting and parameter tempering. This is the reason why most of the web companies today are verifying the type of content they receive and most importantly, from where the contents are originated. It has been thus noted from the above deduction that the major security threat has nothing to do with the Secure Socket Layer rather other layers in the web development program. In order to avoid such threats and other vulnerabilities, initial stages of the web development cycle need to be taken care of.Thus, the main focus of this research paper is to come up with a framework that would help to strengthen the security of the various stages in the web development cycle. For the same, various modules and life cycles have been used.